2003
DOI: 10.1038/sj.onc.1206731
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear accumulation of full-length and truncated adenomatous polyposis coli protein in tumor cells depends on proliferation

Abstract: The adenomatous polyposis coli (APC) tumor suppressor is a nucleocytoplasmic protein. The nuclear accumulation of APC was recently found to vary depending on cell density, suggesting that putative APC function(s) in the nucleus is controlled by the establishment of cell contacts. We report here that the density-dependent redistribution of APC between nucleus and cytoplasm prevails in 6/6 thyroid and colorectal carcinoma cell lines. Moreover, mutated APC lacking known nuclear localization sequences had the simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
4
21
0
1
Order By: Relevance
“…Moreover, our own previous findings (Brocardo et al, 2001) could not be reproduced (data not shown). Two other studies used M-APC antibody (Fagman et al, 2003;Davies et al, 2004), and using this antibody we also observed a redistribution of APC from nucleus to cytoplasm with increasing density of SW480 cells and MDCK cells (Fig 4A; supplementary Fig S5 online). However, when subconfluent or confluent SW480, MDCK or HCT116 cells were fractionated and the nuclear-cytoplasmic distribution of APC was measured by immunoblotting, a density-dependent redistribution of APC was not detected (Fig 4B), although nuclear accumulation was easily detectable after LMB treatment (Fig 3B).…”
Section: Nuclear Localization Of Apc Is Not Affected By Cell Densitysupporting
confidence: 58%
See 3 more Smart Citations
“…Moreover, our own previous findings (Brocardo et al, 2001) could not be reproduced (data not shown). Two other studies used M-APC antibody (Fagman et al, 2003;Davies et al, 2004), and using this antibody we also observed a redistribution of APC from nucleus to cytoplasm with increasing density of SW480 cells and MDCK cells (Fig 4A; supplementary Fig S5 online). However, when subconfluent or confluent SW480, MDCK or HCT116 cells were fractionated and the nuclear-cytoplasmic distribution of APC was measured by immunoblotting, a density-dependent redistribution of APC was not detected (Fig 4B), although nuclear accumulation was easily detectable after LMB treatment (Fig 3B).…”
Section: Nuclear Localization Of Apc Is Not Affected By Cell Densitysupporting
confidence: 58%
“…The N-terminal antibodies Ab7 and Ali 12-28 produced a weaker staining pattern that was mostly cytoplasmic in all cell lines, except for MDCK in which Ali 12-28 displayed a nuclear-cytoplasmic pattern. The antibody most commonly used for IF detection of APC, named M-APC, generated predominantly nuclear staining as recently described (Fagman et al, 2003;RosinArbesfeld et al, 2003;Davies et al, 2004). In the cytoplasm, all antibodies, except for Ab4, detected accumulation of APC at microtubule-associated membrane protrusions (see the MDCK cells in Fig 1C).…”
Section: Unambiguous Detection Of Endogenous Apcmentioning
confidence: 67%
See 2 more Smart Citations
“…Although endogenous fulllength APC exists in both cytoplasm and nucleus (Neufeld and White, 1997;Anderson et al, 2002), the classic NLSs that are thought to facilitate nuclear localization of APC (Zhang et al, 2000) are not present in the M2-APC fragment. The M2-APC region is retained in most truncated forms of APC associated with colorectal cancer and these truncated APC proteins are capable of nucleocytoplasmic shuttling (Fagman et al, 2003). However, the nuclear import ability of these truncated APC proteins has been attributed to the armadillo repeat region (amino acids 334 -625), not the 15-amino acid repeat region (Galea et al, 2001).…”
mentioning
confidence: 99%